Journal of Tort Law (De Gruyter, 2006)
ObjectiveThe Journal of Tort Law aims to be the premier publisher of original articles about tort law. JTL is committed to methodological pluralism. The only peer-reviewed academic journal in the U.S. devoted to tort law, the Journal of Tort Law publishes cutting-edge scholarship in tort theory and jurisprudence from a range of interdisciplinary perspectives: comparative, doctrinal, economic, empirical, historical, philosophical, and policy-oriented. Founded by Jules Coleman (Yale) and some of the world's most prominent tort scholars from the Harvard, Fordham, NYU, Yale, and University of Haifa law faculties, the journal is the premier source for original articles about tort law and jurisprudence. Topics Comparative, doctrinal, economic, empirical, historical, philosophical, and policy-oriented analyses of issues in or related to tort law European Tort Law Comparative Law Foreign and International Law Article formatsScholarly articles, comments and reviews Online Submission of Manuscripts